Molecular Verification of New World Mansonella perstans Parasitemias - Tavares da Silva, Lucyane Bastos; Crainey, James Lee; Ribeiro da Silva, Túllio Romão; Suwa, Uziel Ferreira; Vicente, Ana Carolina Paulo; Fernandes de Medeiros, Jansen; Pessoa, Felipe Arley Costa; Luz, Sérgio Luiz Bessa (Emerging infectious diseases, 2017)
We obtained ribosomal and mitochondrial DNA sequences from residents of Amazonas state, Brazil, with Mansonella parasitemias. Phylogenetic analysis of these sequences confirm that M. ozzardi and M. perstans parasites occur in sympatry and reveal the close relationship between M. perstans in Africa and Brazil, providing insights into the parasite's New World origins.